Pengaruh Kebijakan Deviden, Kebijakan Hutang Dan Kepemilikan Institusional Terhadap Nilai Perusahaan Dalam Prespektif Teori Keagenan - Lailatus Sa’adah (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
This study aims to analyze the effect of dividend policy, debt policy, and institutional ownership on firm value. The population used in this study is in the Property, Real Estate and Building Construction sector companies listed on the Indonesia Stock Exchange (IDX). Dividend policies are proxied by a dividend payout ratio, debt policy is proxied by a debt to equity ratio, institutional ownership is proxied by Institutional ownership, and company value is proxied by the price book value. Based on purposive sampling method that is used to get as many as 51 samples from property sector companies in the 2016-2018 period. The analysis used multiple linear regression which can be processed with SPSS version 25. The results of statistical tests produce that dividend policy has a positive effect on firm value, debt policy has a negative effect on firm value, and institutional ownership has a positive effect on firm value. Simultaneously the variables in this study have a significant effect on firm value.